Latitudinal variation in body size of Agrilus planipennis and relationship with fecundity. (14th May 2013) - Marshall, Jordan M.; Miller, Molly A.; Lelito, Jonathan P.; Storer, Andrew J.
Abstract For many animals with a wide geographical range, latitude is important in determining body size. Additionally, insect body size often has a direct influence on fecundity. Identifying these relationships for a forest pest can add to population dynamics modelling. Agrilus planipennis is a pest of North American Fraxinus species. The relationship between A. planipennis body size and latitude was investigated through field trapping adult A. planipennis in eastern U.S.A., and the relationship between body size and fecundity was investigated through egg production of laboratory‐reared A. planipennis adults. Accumulated growing degree days base 10 °C (GDD10) were calculated and used to identify the influence of local climate on A. planipennis body size. Adult female A. planipennis body size (length and mass) was negatively related to latitude, with larger individuals at southerly sites where the number of days to accumulate 450 and 1000 GDD10 was the lowest. Using positive linear models relating body size and eggs produced, females from southerly sites would potentially produce twice as many eggs as females from northerly sites. Agrilus planipennis population latitudes influenced female body size. Because larger A. planipennis females produced more eggs, there is a potential for populations at southerly sites to increase in density and geography more rapidly than northerly populations.